2007
DOI: 10.1124/dmd.107.016154
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics, Metabolism, and Excretion of the Intestinal Peptide Transporter 1 (SLC15A1)-Targeted Prodrug (1S,2S,5R,6S)-2-[(2′S)-(2-Amino)propionyl]aminobicyclo[3.1.0.]hexen-2,6-dicarboxylic acid (LY544344) in Rats and Dogs: Assessment of First-Pass Bioactivation and Dose Linearity

Abstract: ABSTRACT:The peptidyl prodrug (1S,2S,5R,6S)-2-[(2S)-(2-Amino)propionyl]aminobicyclo[3.1.0.]hexen-2,6-dicarboxylic acid, also known as LY544344, was discovered to improve the oral bioavailability of the parent drug (؉)-2-aminobicyclo[3.1.0]hexane-2,6-dicarboxylic acid (LY354740), a potent group II metabotropic glutamate receptor agonist. This prodrug has been shown to deliver high plasma concentrations of the active drug via intestinal peptide transporter 1 (SLC15A1) (PepT1)-mediated intestinal transport and pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 29 publications
1
17
0
Order By: Relevance
“…The saturable activity of the peptidase(s) was substantiated with the evidence that negligible LY544344 was detected in the cells at low concentrations and that the cellular accumulation ratio of LY354740/LY544344 decreased as the apical LY544344 concentration increased. Recent oral pharmacokinetic studies in rats and dogs showed evidence of saturation of the absorption process at high doses (Perkins and Abraham, 2007).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The saturable activity of the peptidase(s) was substantiated with the evidence that negligible LY544344 was detected in the cells at low concentrations and that the cellular accumulation ratio of LY354740/LY544344 decreased as the apical LY544344 concentration increased. Recent oral pharmacokinetic studies in rats and dogs showed evidence of saturation of the absorption process at high doses (Perkins and Abraham, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Earlier GlySar uptake studies in cell culture models and oral pharmacokinetic studies in rats and dogs indicated that LY544344 had affinity to the intestinal peptide transporter, PEPT1, and was extensively biotransformed into the active moiety, LY354740, before reaching the systemic circulation (Bueno et al, 2005;Rorick-Kehn et al, 2006;Perkins and Abraham, 2007). Bueno et al (2005) reported IC 50 values of 0.30 and 0.12 mM for LY544344 in the GlySar uptake inhibition studies using the Caco-2 and human PEPT1-transfected Chinese hamster ovary cell lines, respectively, suggesting a strong affinity to PEPT1.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Perkins and Abraham, at Eli Lilly, put in practice this approach and delivered the prodrug LY544344, demonstrating the utility of PepT1-targeted nonester prodrugs to overcome poor permeability and low bioavailability. This compound exhibits near-ideal prodrug properties, with good solubility and chemical stability, extensive and reproducible absorption across species, low concentrations of circulating nontoxic prodrug, and pharmacokinetic linearity across a wide dose range [73].…”
Section: Impact Of Pept1 On Absorptionmentioning
confidence: 99%
“…Therefore, it is necessary to increase the absorption rate of Dasatinib as well to decrease the rate of its metabolism. [9][10][11][12] In this current study, a series of amino acid derivatives (see Fig. 2, 144 compounds) as potential prodrugs of Dasatinib were designed with the aim of improving aqueous solubility and therapeutic efficacy, in terms of use of computer-aided drug design methodologies (small molecule flexible docking, virtual screening, three dimensions (3D) database search, lead optimization, 3D-quantitative structure-activity relationship (3D-QSAR), pharmacophore generation and peptide transporter).…”
mentioning
confidence: 99%